2018
DOI: 10.28945/4152
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Dimensions of Identities and Its Impact Upon Member’s Participation in an Online Community of Practice

Abstract: Aim/Purpose: The study aims to explore the dimensions of identities in relation to an online community of practice (CoP) and how the dimensions of identities influence the way teachers behave on their online CoP. Background: One of the emerging approaches for teachers’ professional development is through a form of community of practice, through which teachers learn through collaboration and active learning. In line with the progression in technology, online communities of practice have been widely accepted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
0
8
3
1
Order By: Relevance
“…Meanwhile, [29] offer the concept of identity as 'who or what someone is, the various meanings someone can attach to oneself or the meaning attributed to oneself by others' (p. 282). [30] conducted her research using a qualitative approach which involved data generation from in-depth interviews with her respondents. This study utilised the dimensions of identities as a framework, and changed the sub-categories that arose from the qualitative analysis into a set of questionnaires.…”
Section: Factors Influencing the Level Of Participation In Online Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, [29] offer the concept of identity as 'who or what someone is, the various meanings someone can attach to oneself or the meaning attributed to oneself by others' (p. 282). [30] conducted her research using a qualitative approach which involved data generation from in-depth interviews with her respondents. This study utilised the dimensions of identities as a framework, and changed the sub-categories that arose from the qualitative analysis into a set of questionnaires.…”
Section: Factors Influencing the Level Of Participation In Online Communitiesmentioning
confidence: 99%
“…This study utilised the dimensions of identities as a framework, and changed the sub-categories that arose from the qualitative analysis into a set of questionnaires. The aims of this study were to identify students' identities in relation to their participation in online communities using the four dimensions of identities [30] and to measure the relationships between the different dimensions of identities.…”
Section: Factors Influencing the Level Of Participation In Online Communitiesmentioning
confidence: 99%
“…This lack of recognition for the work required to engage in the elaborated ways found in the threads analysed in this paper may present a problem for sustaining teacher professional development online communities over time. If the kinds of rich professional discussions examined here are to be encouraged, increased professional use of social media by means of "invisible" digital work, as highlighted by Khalid (2018), needs to be addressed by teachers, politicians, school leaders, and other stakeholders in terms of the implications for teachers, teaching and schooling more generally.…”
Section: Discussionmentioning
confidence: 99%
“…As initially mentioned, the body of literature acknowledging the unique conditions that social media groups offer to teachers for sharing and professional support is fast growing (Bodell & Hook, 2011;Goodyear et al, 2014;Kelly & Antonio, 2016;Khalid, 2018;Lantz-Andersson et al, 2018;Macià & García, 2016Ranieri et al, 2012;Rodesiler, 2015;Trust et al, 2016;Tsiotakis & Jimoyiannis, 2016;Wesely, 2013). Studies this far have identified two main patterns of interaction: one targeted at information sharing and the other focusing on social relations and support.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Often, family responsibility is viewed as a hindrance for teachers in giving commitment to work outside of school hours, specifically in designing technology-based teaching. Khalid (2018) also stated that participation of teachers in online learning is influenced by their personal traits, such as their age, marital status as well as their responsibilities towards their children. Lifestyle and demographic characteristics were also discussed by (Moon, 2018;Li & Huang, 2016) as factors influencing teachers' use of technology for learning activities using technology.…”
Section: Personal Factormentioning
confidence: 99%